Lo sperimentalismo narrativo di Federico De Roberto (FedOA - Federico II University Press, 2026)
This volume collects the essays presented at the study conference Federico De Roberto’s Narrative Experimentalism: Research and Perspectives, held on 23-24 May 2024 at the University of Naples “Federico II”.